Analysis of amateurs and professional translator's renderings using the appraisal method by Coffin & O'Halloran for determining between the two groups. - Vera Pino, Jennifer Karina (2017)
The present document is a case study carried out in the field of translation by applying some methodology on the light of discourse analysis. These are basically the Appraisal method plus some schema theory basis, added to the consideration of features on Bloom’s taxonomy at different levels of analyses. The objective of this case study is to apply the aforementioned knowledge in order to model a strategy for analyzing texts which have been translated from Spanish into English, in which five participants –among professional and amateurs, both supplied with certain experience in the field of translation- contributed with renderings for the sake of establishing a line of contrast between the target texts resulting from the two groups–professional and amateurs- terms used to referred to translators with either a formal or informal training in the field, respectively. Such analyses will contribute to build a narrow path from the already existing methodology on discourse analysis bases applied to the translation field.